In vitro chondrogenic induction promotes the expression level of IL-10 via the TGF-β/SMAD and canonical Wnt/β-catenin signaling pathways in exosomes secreted by human adipose tissue-derived mesenchymal stem cells - Semerci Sevimli, Tuğba; Inan, Ulukan; Mantar, Dilara; Guler, Kubra; Ahmadova, Zarifa; Gulec, Kadri; Topal, Ahmet Emin (Cell biochemistry and biophysics, 2024)
Current treatment approaches cannot exactly regenerate cartilage tissue. Regarding some problems encountered with cell therapy, exosomes are advantageous because of their “cell-free” nature. This study examines the relationship between IL-10 and TGF-β and Canonical Wnt/β-catenin signal pathways in human adipose tissue-derived MSCs exosomes (hAT-MSCs-Exos) after in vitro chondrogenic differentiation. Human adipose tissue-derived mesenchymal stem cells (hAT-MSCs) and, as a control group, human fetal chondroblast cells (hfCCs) were differentiated chondrogenically in vitro. Exosome isolation and characterization analyses were performed. Chondrogenic differentiation was shown by Alcian Blue and Safranin O stainings. The expression levels of IL-10, TGF-β/SMAD signaling pathway genes, and Canonical Wnt/β-catenin signaling pathway genes, which play an essential role in chondrogenesis, were analyzed by RT-qPCR. Conditioned media cytokine levels were measured by using the TGF-β and IL-10 ELISA kits. IL-10 expression was upregulated in both chondrogenic differentiated hAT-MSC-Exos (dhAT-MSC-Exos) (p < 0.0001). In the TGF-β signaling pathway, TGF-β (p < 0.0001), SMAD2 (p < 0.0001), SMAD4 (p < 0.001), ACAN (p < 0.0001), SOX9 (p < 0.05) and COL1A2 (p < 0.0001) expressions were upregulated in dhAT-MSC-Exos. SMAD3 expression was upregulated in non-differentiated hAT-MSC-Exos. In the Canonical Wnt/β-catenin signaling pathway, WNT (p < 0.0001) and CTNNB1(p < 0.0001) expressions were upregulated in dhAT-MSC-Exos. AXIN (p < 0.0001) expression was upregulated in non-differentiated hAT-MSC-Exos. TGF-β and IL-10 levels were higher in dhAT-MSCs) (p < 0.0001). Related to these results, IL-10 may induce TGF-β/SMAD and Canonical Wnt/β-catenin signaling pathways in hAT-MSC exosomes obtained after chondrogenic differentiation. Therefore, using these exosomes for cartilage regeneration can lead to the development of treatment methods.
Gesehen am 27.01.2025